Development of methodology of accounting and control processes in the digital economy - A. V. Bodiako (Управление)
A technology for the formation of information-security mission of accounting and control processes in the digital conomy and the changed requirements for the formation of information for management decisions, combining in a single information-digital “shell” accounting, control, analytical and other iterations, which should contribute to a better compilation of different reporting formats, has been presented. On the basis of a comparative assessment of approaches and opinions of Russian and foreign scientists on the essence of this issue, conclusions, regarding the need to improve the tools of accounting engineering in terms of aggregation of information on the accounts and the accounts themselves, have been drawn.The proposed technology of accounting and control processes is based on a risk-oriented method that allows to identify previously veiled shortcomings of the functioning of accounting subsystems (statistical, production and technical, financial and evaluation, management). Having identified the business risk by the Classifier, the analyst forms a risk map in which external and internal threats to the growth and development of the holding are grouped, decisions on which risks are formed, there is a need to minimize threats, optimize solutions. This opportunity provides analysts with the necessary impetus to establish their causal basis for further development of the concept of minimizing business risks.It has been proposed to develop the methodology of accounting and control processes using the provisions of the theory of comparativistics. The model of information support of the decision of tactical and strategic tasks in the large company of holding type allowing us to transform successfully business processes and “digital” models of their management by development of methodology of accounting-analytical and control-regulatory support of all cycles (stages) of strategy implementation has been developed. As a result, this support will meet the modern requirements of management practice in a broad understanding of the meaning and significance of this process.